The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/idh.12587
|View full text |Cite
|
Sign up to set email alerts
|

Risk indicators of long‐term outcome of implant therapy in patients with a history of severe periodontitis or no history of periodontitis: A retrospective cohort study

Abstract: Objective The aim of this retrospective cohort study was to assess factors associated with peri‐implant disease in partially edentulous patients with a history of severe periodontitis or no history of periodontitis. Methods Partially edentulous patients with a history of severe periodontitis/without history of periodontitis who received implant surgery within the past 6 to 8 years were recalled. Clinical and radiographic examinations were recorded. Periodontal probing depth, marginal bone loss (MBL) and peri‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…One study found a significant difference in favour of a counter‐rotational powered toothbrush in terms of peri‐implant mucosal inflammation and implant survival compared with manual toothbrushing (Truhlar et al, 2000). One case–control study indicated that the frequency of tooth brushing (at least twice a day vs. at most once a day) had no impact on peri‐implant PD, MBL and BOP (Alhakeem et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…One study found a significant difference in favour of a counter‐rotational powered toothbrush in terms of peri‐implant mucosal inflammation and implant survival compared with manual toothbrushing (Truhlar et al, 2000). One case–control study indicated that the frequency of tooth brushing (at least twice a day vs. at most once a day) had no impact on peri‐implant PD, MBL and BOP (Alhakeem et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The other RCT, comparing sonic versus manual toothbrush over a 1‐year trial, concluded that both toothbrushes maintain peri‐implant tissue health over time (Swierkot et al, 2013). Finally, the case–control study indicated that the frequency of tooth brushing (at least twice a day vs. at most once a day) had no impact on peri‐implant PPD, MBL, and BOP (Alhakeem et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Two articles reported different outcomes on the same study population (M. Roccuzzo et al, 2010, 2012), and another two articles reported outcomes of the same study population at different follow‐up intervals, at 10 (M. Roccuzzo et al, 2014) and 20 years (A. Roccuzzo et al, 2022). Twelve studies compared patients regularly attending the recommended SPC versus not attending or attending SPC visits irregularly (Aguirre‐Zorzano et al, 2013; Alhakeem et al, 2022; Ferreira et al, 2006; Frisch et al, 2020; Hu et al, 2020; Monje et al, 2017; Rinke et al, 2011; A. Roccuzzo et al, 2022; M. Roccuzzo et al, 2010, 2012, 2014; Roman‐Torres et al, 2019); one RCT compared four different SPC protocols over a 1‐year study period (Ziebolz et al, 2017), and one study compared patients with or without deep residual periodontal pockets during the SPC (Cho‐Yan Lee et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A comparable study also reported that patients who have a history of severe periodontitis, insufficient peri-implant keratinized mucosa, and implants placed in bone-grafted areas are more likely to develop PI. 14 Despite the connection between a history of periodontitis and PI, little is known about preventing PI in patients with such a history.…”
Section: Introductionmentioning
confidence: 99%